THE SYSTEMATIC REVIEW OF GLAUCOMA AND ITS ASSOCIATIONS WITH FEMALE REPRODUCTIVE FACTORS - Paranoan, Anelsa; Chaesar Male, Hendro Dwiky (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Estrogen may have a neuroprotective role in glaucoma, and estrogen insufficiency is thought to contribute to glaucomatous damage through both mechanical and vascular processes. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 93 articles, whereas the results of our search on SCIENCE DIRECT brought up 76 articles. The results of the search conducted for the last year of 2014 yielded a total 41 articles for PubMed and 26 articles for SCIENCE DIRECT. In the end, we compiled a total of 6 papers, 4 of which came from PubMed and 2 of which came from SCIENCE DIRECT. We included six research that met the criteria. Conclusion: In summary, a longer duration of OC usage may be related with a higher risk of OAG; however, it is unclear if OC use in general raises the risk of OAG or whether this potential association is mediated by IOP. An earlier age at natural menopause may increase the incidence of OAG. Most significantly, PMH use may be related with a lower IOP, and the estrogen-only kind of PMH may be associated with a lower risk of OAG.